Republic of Equatorial Guinea : Staff-Monitored Program. (IMF Staff Country Reports; Country Report ;, 2018)
On May 10, 2018, the IMF approved a Staff-Monitored Program (SMP) for Equatorial Guinea, covering the period January-July 2018. The SMP will help in building an adequate track record of performance for a potential IMF-supported program. The SMP aims to reduce further the fiscal deficit, increase non-oil revenue, and address critical public financial management weaknesses, while protecting social spending. The SMP also envisages measures to improve the business climate and foster economic diversification. The program will aim to lay the basis for improving governance and transparency in public administration and the hydrocarbon sector. The program will also provide a framework to strengthen public sector capacity through technical assistance provided by the IMF.